Multiple Sclerosis Injection in the Form of Use Disease Modifying Drugs, Why Is the End? - Terzi, Murat; Sen, Sedat (Sage Publications Ltd, 2017)
…
9th Congress of the Pan-Asian-Committee-for-Treatment-and-Research-in-Multiple-Sclerosis (PACTRIMS) -- OCT 27-29, 2016 -- Bangkok, THAILAND